2006
DOI: 10.1038/ncb1406
|View full text |Cite
|
Sign up to set email alerts
|

APCcdh1 activity in mouse oocytes prevents entry into the first meiotic division

Abstract: SummaryFully-grown mammalian oocytes maintain a prophase I, germinal-vesicle stage arrest in the ovary for extended periods before a mid-cycle luteinizing surge induces entry into the first meiotic division. Cdh1 is an activator of the Anaphase-Promoting Complex (APC), and APC cdh1 is normally restricted to late M -early G1 of the cell cycle. Here we find that APC cdh1 is active in mouse oocytes and is necessary to maintain prophase arrest.Fully-grown mammalian oocytes remain arrested at prophase I within antr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
182
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(191 citation statements)
references
References 11 publications
7
182
1
1
Order By: Relevance
“…The importance of APC/C Cdh1 for restraining Cdk1 through low-level cyclin B1 degradation was initially demonstrated in vitro using morpholino antisensemediated depletion of Cdh1 in fully grown oocytes denuded of their surrounding follicular cells (Reis et al 2006). It was found that such Cdh1-depleted oocytes exhibited an increased susceptibility to undergoing GVBD even under conditions in which cAMP levels were chemically sustained using the phosphodiesterase inhibitor, milrinone.…”
Section: Cdh1mentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of APC/C Cdh1 for restraining Cdk1 through low-level cyclin B1 degradation was initially demonstrated in vitro using morpholino antisensemediated depletion of Cdh1 in fully grown oocytes denuded of their surrounding follicular cells (Reis et al 2006). It was found that such Cdh1-depleted oocytes exhibited an increased susceptibility to undergoing GVBD even under conditions in which cAMP levels were chemically sustained using the phosphodiesterase inhibitor, milrinone.…”
Section: Cdh1mentioning
confidence: 99%
“…APC/C Cdh1 -mediated proteolysis suppresses cyclin B1 levels to sustain G2/prophase arrest (Reis et al 2006). Conversely, Emi1 and securin serve to limit such proteolysis, thereby allowing cyclin B1 accumulation and Cdk1 activation required for GVBD (Marangos et al 2007, Marangos & Carroll 2008.…”
Section: Cdk1mentioning
confidence: 99%
See 1 more Smart Citation
“…Microinjection of oocytes is a powerful method to study mechanisms that regulate meiotic maturation 10,11,12,13 . This method provides an economical way to test hypotheses prior to making a large investment in developing transgenic and targeted mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Les preuves montrant que l'APC/C est requis en méiose I sont indirectes, et aucun activateur de l'APC/C spécifique de la méiose n'a été mis en évidence chez les mammifères, comme cela a été le cas dans d'autres espèces [32]. Il semblerait que l'activateur requis pour l'entrée en méiose I soit Cdh1 [33]. Un rôle difficile à concilier avec le fait que Cdh1 est requis pour la sortie de mitose, et que des substrats de l'APC/ C qui sont dégradés de manière dépendante de Cdh1 peuvent cependant …”
Section: Questions Ouvertes Et Paradoxes Méiotiquesunclassified